Study of the extraction of tannic acid from pomegranate peels and its applications in removing chromium (III) ion from industrial water (Journal of the College of Basic Education, 2022)
The research included a study of extracting a natural substance (tank acid) from pomegranate scales, which is used as a basic substance in treating water pollution with heavy elements, using liquid chromology technology with high performance. On the other hand, the use of spectral techniques such as UV -visual radiation, and infrared technology, tank acid has been estimated by high -performance liquid chromatography and a separation column of type (5µm, 250 CM, 4.6M) C18 using UV at a wavelength of 265 nm, The detention time was 6.348 minutes, the amount of relative, relative deviation 1.28% and the rate of retrieval 98.2,